Tidal Analysis and Implementasion of an Internet of Things (IoT) Sea Level Monitoring Device in Coastal Region - Kusuma, Hollanda Arief; Egistian, Farista; Cintra, Allsay Kitsash Addifisyukha; Setyono, Dwi Eny Djoko (Universitas Diponegoro, 2024)
Monitoring the sea level is crucial for the protection of coastal communities and infrastructure. Instruments that can record and transmit the sea level in real time are essential for preventing potential disasters. This study presents the design, construction, and evaluation of an instrument for measuring sea level using a pressure sensor, a microcontroller, and a GSM module. The sea level analyzed using T Tide analysis. The instrument's accuracy was established through a calibration process, resulting in a sensor reading accuracy of 96.76% and a low root mean square error of 3.24 cm. The linear regression model confirmed the strong correlation between sensor readings and actual water depth, with a coefficient of determination of 0.999. The instrument achieved an accuracy of 96.76% and a low root mean square error of 3.24 cm. Field testing over three days showed the instrument's reliability in measuring sea levels, with an accuracy rate of 91.93% and an root mean square error of 8.07 cm with a packet loss of 7.86%. The study area had mixed semidiurnal characteristics, with water levels ranging from 60.1 cm to 209.55 cm. Significant constituents such as principal lunar diurnal constituent (K1) and Principal lunar semidiurnal (M2) dominate the tidal patterns, each with distinct frequencies, amplitudes, and signal-to-noise ratios. This research provides a precise and cost-effective instrument for measuring water depth, which is suitable for coastal management, environmental monitoring, and scientific investigation.